Principles of movement - Anderson, Brent PT, PhD, OCS, NCPT (SLACK Incorporated, 2024)
"From the founder of Polestar Pilates, Principles of Movement is a practical resource guide on movement science for movement practitioners, therapists, and anyone looking for a practical and easy approach to assess, facilitate, and enhance movement. With applications in physical therapy, occupational therapy, athletic training, kinesiology, physical education, Pilates training, yoga training, dance education, and more, Principles of Movement is designed to help the movement practitioner improve the quality of their practice by better understanding the integrated model of movement assessment and movement facilitation. The text focuses on how to facilitate the quality of movement-not just the quantity. Author Dr. Brent Anderson draws upon his 30 years of experience in rehabilitation and movement science, showing the strong correlation between motor control and biomechanics, and integrating new work on fascia, pain interpretation, and behavioral elements associated with movement. Principles of Movement is designed to facilitate problem solving and movement enhancement through a deeper understanding of universal movement principles. What's included in Principles of Movement: How to harness tools such as breath, mobility, dynamic alignment, control, and coordination to improve movement efficiency and performance, minimize injuries, and increase personal satisfaction through successful movement experiences without pain Examples, practical applications, and teaching tips for movement practitioners A guide to critical reasoning that applies the Principles of Movement algorithm to exercise selection and treatment planning Teaching aids and applications that can be immediately integrated into practice, including verbal, tactile, and imagery cueing Principles of Movement provides students and practitioners alike with a framework to evaluate, facilitate, and optimize the quality of movement"--